2021
DOI: 10.1155/2021/5571733
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Stress Mechanisms behind Resveratrol: A Multidimensional Analysis

Abstract: Over the past decade, oxidative stress was shown to be a key factor for various diseases. The term “antioxidant” also rapidly gained attention worldwide, viewed as beneficial in disease prevention. Resveratrol (RSV), a natural polyphenol, is a plant antitoxin formed in response to harmful environmental factors such as infection and injury. This antitoxin is found in grapes, strawberries, peanuts, or herbal medicines and exhibits many pharmacological effects involved in antitumor, anti-inflammatory, antiaging, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 109 publications
1
22
0
Order By: Relevance
“…Concerning the histopathological changes, the results confirmed the ability of H2O2 to induce progressive adverse effects on the components of the cell as illustrated in figures belonging to group G1, maybe due to LPO and oxidative stress, which led to increases in intracellular calcium, activates membrane phospholipid proteases, mitochondrial dysfunction (3), glomerular tuft degeneration and promote the initiation of autophagy and apoptosis in the different pathway (29). Current observations showed that resveratrol rescued renal histopathological damage against H2O2.…”
Section: Discussionsupporting
confidence: 66%
“…Concerning the histopathological changes, the results confirmed the ability of H2O2 to induce progressive adverse effects on the components of the cell as illustrated in figures belonging to group G1, maybe due to LPO and oxidative stress, which led to increases in intracellular calcium, activates membrane phospholipid proteases, mitochondrial dysfunction (3), glomerular tuft degeneration and promote the initiation of autophagy and apoptosis in the different pathway (29). Current observations showed that resveratrol rescued renal histopathological damage against H2O2.…”
Section: Discussionsupporting
confidence: 66%
“…Although resveratrol is able to directly scavenge a variety of free radicals, its main antioxidant effect is more properly due to its regulation of redox genes [20]. SOD1 is one of the three superoxide dismutases known to catalyse the dismutation of superoxide (O 2 − ) to hydrogen peroxide (H 2 O 2 ) and O 2 ; at the same time, GPX1 and CAT catalyse the rapid decomposition of H 2 O 2 while GSR is involved in the glutathione-dependent antioxidant system by reducing oxidized glutathione [57].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the well-established role of oxidative stress in Cd reproductive toxicity, developing defence strategies using antioxidants is a growing field of study [19]. Resveratrol (Res; 3,4,5-trihydroxy-trans-stilbene), a phytoalexin produced by plants, is one of the most studied polyphenol with well-established antioxidant properties [20]. Several studies in various species provided evidence that Res could act as a powerful antioxidant being able to prevent the disruption of oocyte redox homeostasis and the decline of the oocyte quality and to improve oocyte IVM, IVF and subsequent embryonic development rates [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, there must be an equilibrium between oxidants and antioxidants in living organisms and any deviation in this balance can be harmful either as oxidative stress or antioxidative stress. 1,3 Medicinal plants have attracted immense attention due to their high antioxidant capacity. A large amount of evidence has shown that there is a positive relationship between flavonoid and phenolic contents and antioxidant activity of plant organs.…”
Section: Introductionmentioning
confidence: 99%